2001
DOI: 10.1054/bjoc.2000.1623
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant interferon alpha 2b in high risk melanoma – the Scottish study

Abstract: In 1989, the Scottish melanoma group initiated a randomized trial, comparing observation alone with 6 months' therapy with low dose interferon α (given subcutaneously 3 MU day –1 , thrice weekly), for patients with primary melanomas of at least 3 mm Breslow thickness, or with evidence of regional node involvement. The trial was closed in 1993 with only 95 eligible patients randomized. There were no toxic deaths, and no patient failed to complete the treatment for reasons of toxicity. 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(39 citation statements)
references
References 7 publications
0
35
0
4
Order By: Relevance
“…Concerning low-dose therapy in stage III disease, only one of 6 trials revealed improvement in progression-free and overall survival [375,396,399,[401][402][403]. Administration of high-dose therapy seems to be justified at stage IIIB and IIIC despite increased toxicity.…”
Section: Adjuvant Interferon Therapymentioning
confidence: 99%
“…Concerning low-dose therapy in stage III disease, only one of 6 trials revealed improvement in progression-free and overall survival [375,396,399,[401][402][403]. Administration of high-dose therapy seems to be justified at stage IIIB and IIIC despite increased toxicity.…”
Section: Adjuvant Interferon Therapymentioning
confidence: 99%
“…Again, there was a clear advantage for LDI in terms of disease-free survival, and a trend towards improved overall survival (Grob et al, 1998). Similar results with only 6 months treatment are published in this issue by the Scottish Melanoma Group, although the relatively small numbers recruited to their study preclude meaningful statistical analysis (Cameron et al, 2001). The UKCCCR AIMHIGH study, which has recently closed to recruitment, will provide more evidence on the effects of LDI in the stage IIB and III population.…”
mentioning
confidence: 52%
“…This chapter focuses on those studies that have compared interferon to observation only and these are summarised in table 1. Of the 13 published trials, 7 have demonstrated a benefit for IFN over observation in terms of disease free survival (DFS) and 2 have demonstrated an overall survival (OS) benefit (E1684 and DeCOG) (Kirkwood et al 1996;Garbe et al 2008) The Scottish MG trial demonstrated benefits for both DFS and overall survival at 2 years but this diminished with longer follow up and was not statistically significant at 6 years (Cameron et al 2001). A meta-analysis of 12 trials was reported in 2003 including 10 trials with IFN compared to observation and 2 studies comparing IFN to a GMK vaccine (Wheatley et al 2003).…”
Section: Adjuvant Treatmentmentioning
confidence: 99%